The Chivalric Romance in the Age of its Neoliberal Reproducibility: The Orlando Furioso Transcodified in Marvel’s Iron Man Saga - Balestrino, Alice (REDEN. Revista Española de Estudios Norteamericanos, 2023)
This article interprets Marvel’s Iron Man saga, including the Avengers’ chapters, as a particularly interesting instance of the latest stage of American exceptionalism, here understood as imbricated in the neoliberal society. This reading is built upon the hypothesis that the Avengers’ adventures may be viewed as a twenty-first century development of the chivalric romance and of the knights’ quests, both in narrative and ideological terms. A key facet of this interpretation lies in the realization that technological reproducibility is a crucial aspect both of neoliberalism and of the Marvel’s saga, the latter being the articulation of the traditional chivalric genre according to the contemporary neoliberal principles. Against this background, the article presents the Iron Man movies in continuity with the literary tradition established by Ludovico Ariosto’s Orlando Furioso.